THE VAYU PURANA AS AN OBJECT OF LINGUISTIC CULTURAL HERITAGE - Akhyadov, Elman; Goncharov, Vitaly; Makushkin, Sergey (Revista Inclusiones, 2020)
Against the backdrop of globalization, which encompasses all spheres of modern culture, it is impossible to stay in a confined civilizational space in the presence of religious diversity existing in the world. In this context, research into the religious and worldview paradigms of Hinduism presented in its literary heritage as one of the sources is highly relevant, especially considering the fact that Hinduism is, in fact, an umbrella term denoting a vast array of faiths practiced by over 800 million people in the world, 96% of whom are Indian. The article analyzes the role of the Puranas in the Hindu tradition, provides an overview of the Puranic literature and its main specific features and summarizes the characteristics of the Vayu Purana as a monument of Puranic literature. The authors draw a conclusion that the Vayu Purana can be considered one of the most outstanding pieces of medieval Indian literature.